2020
DOI: 10.1093/molehr/gaaa078
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes associated with endometrial cell ageing

Abstract: Aging of the uterine endometrium is a critical factor that affects reproductive success, but the mechanisms associated with uterine aging are unclear. In this study, we conducted a qualitative examination of age-related changes in endometrial tissues and identified candidate genes as markers for uterine aging. Gene expression patterns were assessed by two RNA sequencing experiments using uterine tissues from wild type (WT) C57BL/6 mice. Gene expression data obtained by RNA-sequencing were validated by real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…It has been reported that deletion of Cxcl14 in mice could accelerate skeletal myogenesis by promoting cell cycle withdrawal, which may be a promising target for developing therapeutics to treat aging-related muscle wasting ( Waldemer-Streyer et al, 2017 ). And it has also been identified as a candidate marker for endometrial aging ( Kawamura et al, 2021 ). Besides, cxcl14 is an essential factor in the initial and maintenance of pain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that deletion of Cxcl14 in mice could accelerate skeletal myogenesis by promoting cell cycle withdrawal, which may be a promising target for developing therapeutics to treat aging-related muscle wasting ( Waldemer-Streyer et al, 2017 ). And it has also been identified as a candidate marker for endometrial aging ( Kawamura et al, 2021 ). Besides, cxcl14 is an essential factor in the initial and maintenance of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that CXCL14 overexpression promotes NK cell migration, cytotoxicity and infiltration [ 40 ], and is involved in thrombosis and platelet migration [ 41 ]. In addition, new evidence suggests that high expression of CXCL14 may cause endometrial cell aging [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes may be related to endometrial steroid receptors, altered blood flow, stromal angiosclerosis and other processes described in other animal species ( Melnick & Rosenwacks, 2018 ). A recent study showed that gene expression of proteins related to infammation and stemness is significantly higher in endometrial samples of patients in their 40s when compared with women in their 20s ( Kawamura et al ., 2021 ). Thus, these genes may be used as markers for endometrial aging and age-related infertility.…”
Section: Discussionmentioning
confidence: 99%